KAJIAN FAKTOR PENENTU MASA SIMPAN PRODUK BUBUK BUMBU DENGAN CARRIER MALTODEKSTRIN DE-12 DAN DE-18 - Widjajaseputra, Anna Ingani; Srianta, Ignatius; Handayani, Yashinta Natalia (Widya Mandala Surabaya Catholic University, 2003)
Seasoning powder is very useful in modern life. Seasoning powder can make certain food preparation easier, such as fried chicken, fried shrimp etc. The problem are discoloration and free flowing ability due to the increasing of reducing sugar content during storage. The objective of this research is to study on dominant factors of shelf-life of seasoning powder using maltodextrine, DE-12 and DE-18 as